A chemoenzymatic strategy for the efficient synthesis of amphenicol antibiotic chloramphenicol mediated by an engineered l-threonine transaldolase with high activity and stereoselectivity. Issue 3 (21st December 2022) - Xu, Lian; Nie, Dan; Su, Bing-Mei; Xu, Xin-Qi; Lin, Juan
Abstract : Chemo-enzymatic route for chloramphenicol. Abstract : The synthesis of chloramphenicol, a kind of amphenicol antibiotic with broad-spectrum antibacterial activity, is challenging due to its stereochemistry. Here, we have designed a four-step chemoenzymatic strategy, including a biocatalytic step mediated by l -threonine transaldolase from Pseudomonas sp. (PsLTTA) to convert 4-nitrobenzaldehyde (1 ) to (2 S, 3 R )-2-amino-3-hydroxy-3-(4-nitrophenyl)propanoic acid (2 ) followed by a three-step chemical reaction to obtain chloramphenicol. A rational design of PsLTTA was devised by reshaping the substrate binding pocket and substrate access channel, resulting in the best variant PsLTTA-N35A/C57I/F59A/H69F (PsLTTA-Mu9), which achieved a 7.1-fold higher yield of 2 than wild-type PsLTTA. After coupling with ScADH/CbFDH to remove the byproduct acetaldehyde and optimizing the reaction conditions, the whole-cell catalyst BL21(PsLTTA-Mu9/ScADH/CbFDH) could synthesize 200 mM of 2 in four hours with 99% conversion and 97.7% de, delivering the highest time–space yield (11.3 g L −1 h −1 ) ever reported. Finally, the chemoenzymatic approach was applied for the gram-scale synthesis of 5 with a high overall yield (54%). The success of this strategy demonstrates the great advantage of the chemoenzymatic approach in the asymmetric synthesis of chloramphenicol and may contribute to its industrial synthesis.